تحديد التلوث البكتيرى والبيئى ضمن مدينة سامراء - العيساوى، حارث احمد مصطفى محمد (2012)
This study had been done on the eastern side of Tigris in Samarra for a distance approximately 5Kms, The places had been chosen along the river within the area of study in eight months since November 2010 till June 2011, the aim of this study was discovering some species of the Bacteria which cause Pollution to river and Includes the total number count of an aerobic bacteria (TPC) , total coliform bacteria and fecal coliform bacteria and diagnosis some species of bacteria which present in water of the river in Samarra in the area of study which distented to 5Kms form the main water supply of the city till the floating bridge in the south Samarra's Dam. Beside the study of some physical and chemical factors the resistance of environmental and clinical bacteria for some antibiotics had been tested. The results of study explained that the temperature values of air and in places water in rang between (13ͦ.3-33ͦ) for air ,and (10ͦ-27ͦ) for water, while the values of Turbidity between (0.1-16.24)NTU, The highest values recording during March and electrical conductivity in places-water between (370-660)microseminse , the highest values was in December. The sample for different places shown PH, in arrange between (7.1-9.1). The Oxygen Dissolved in places water was in arange between (4.4-10.0)mg/L , the value was elevated in winter. The Biological oxygen demand ( BOD) so the data above give as satisfactory that water of the river at that places is good and may considered as a source for production clean water by using ordinary protect according to the world which dependable in classification of surface water . For the number of fecal colonic bacteria , the highest average was in summer in the third place where sewage water pour-into during May and June (1.44-1.46)×103 cell/100ml respectively, while the lowest for this bacteria recorded during winter for all the places and the lowest average was in December and January it was (0.3 - 0.62) )×103 cell/100ml. The results of separation and diagnosis in places water which involved in the study , separation and diagnosis for Six species of gram negative of colonic bacteria gained. Escherichia ,Salmonella, Shigella ,Klebsiella, Proteus, Pseudomonas and two species of gram positive which are streptococcus , staphylococcus . When sensitivity test for antibiotics had been done for a group environmental separators for 12 antibiotics found that environmental separators was restante to penicillin group involve Nitrofurantion, Carbenicilln ,penicillin ,and It restante to Nitrofurantoin, Cefotaxime ,Cephalexin , Tetracycline,Clindamycin ,Trimethoprim While had been sensitive to Chloramphenicol , Novobiocin , Kanamycin , Azithromycin .